Korean Version of the Functional Assessment of Cancer Therapy (FACT)-Vanderbilt Cystectomy Index (VCI): Translation and Linguistic Validation - Kim, Myong; Lee, Hahn-Ey; Kim, Sung-Han; Cho, Sung Yong; Jeong, Seong Jin; Oh, Seung-June; Cookson, Michael S.; Ku, Ja Hyeon (Urology Journal, 2014)
Purpose: To develop a Korean version of the Functional Assessment of Cancer Therapy (FACT)-Vanderbilt Cystectomy Index (VCI) from the original English version, with subsequent linguistic validationin Korean patients who underwent radical cystectomy with urinary diversion. Materials and Methods: Translation and linguistic validation were carriedout between January and May of 2013, which consisted of the following stages:(1) permission for translation;(2) forward translation;(3) reconciliation;(4) backward translation;(5) cognitived ebriefing and(6) final proof-reading. Results: During the forward translation phases,word ssuch as "bother","spend time", "support", "coping" and "concern" were adjusted to be more comprehensible to the target population. There conciled Korean version was accepted without certain objections because the original version and the backward translation were almost congruent exceptfor minor differences in a subset of questions. The translation was tested using 5 Korean-speaking subjects. The subjects took an average of 8.2 minutes to complete the questionnaire, without difficulty and found thequestionnaire clear andeasyto understand. The panel discussed each of the issues raised by subjects and most terms were judged by the panel as to not require further changes because the overall comprehension levels were relatively high and because the translated terms were accurately rendered in the target languages. Conclusion: This report has demonstrated that despite translation difficulties, the linguistic validation of the FACT-VCI in the Korean language was successful. The next step is to assess the psychometric properties of the Korean version of FACT-VCI.